Aspects of social identity, self concept, self esteem, self functioning and gender aspects (part 7) - Yahaya, Azizi (2012)
Global self-esteem may be a composite of several individual areas of self evaluation. Each of these subareas can be assessed separately and there is a scale for measuring three aspects of self-esteem such as performance self-esteem, appearance self-esteem and social self-esteem